Dynamics Population of Yellow fin Tuna Thunnusalbacares in Bone Bay, Indonesia - Jalil, Achmar Mallawa, Faisal Amir, Safruddin (International Journal of Advanced Science and Technology, 2020)
The finding the study to measure some key characteristics of the population dynamics of yellowfin tuna.  A total of 12.936samples were collected using handline fishing and measured forfor k length with a precision of 1 cm. Growth parameters of von Bertalanffy were identified using ELEFAN method and FiSAT II software, while natural mortality was obtained according to Pauly’s empirical formula. The range of fishing mortality also accounted for the parameter of the population dynamics. Yield per Recruit (Y/R) was calculated using the standard formulation of Beverton and Hold. The estimated growth parameter corresponded to length infinity = 220 cm and growth rate = 0,37 per year. The resulting index of growth performance was 4,261. Total mortality was found at 2,25 per year-1, natural mortality at 1,71 per year-1, fishing mortality at 0,54 per year-1and exploitation rate at 0,76 per year-1. These findings, which highlight the importance of research in connection with population dynamic parameters, can set out the guideline for yellow fin tuna management in Bone Bay.